PERILAKU ANAK AGRESIF: ASESMEN DAN INTERVENSINYA - Tentama, Fatwa (Universitas Ahmad Dahlan, 2012)
The purpose of this study 1. To find out the behavior, situation and condition of aggressive children and the environment. 2. Determining appropriate interventions and programs as needed. 3. How the application of child management training program in order to reduce ag-gressive behavior. The subject is the childs parents, community leaders and the surrounding communities. Qualitative research method is a method by observation and in-depth interviews and training approach using the method of Albert Banduras social learning to use the principle of modeling (modeling transfer) will provide many opportunities for trainees to learn to be a figure / model that would be an example of children as aggressive efforts to educate children in the neighbor-hood core. The final results are expected in the end the participants know and be aware of the situa-tion, the childs condition and its surroundings and be able to implement training programs pro-vided to deal with children effectively in reducing aggressive behaviors of children. Keywords: aggressive child, child management training program